TRPV1 in chronic pruritus and pain: Soft modulation as a therapeutic strategy - Fernández-Carvajal, Asia; Fernández-Ballester, Gregorio; Ferrer-Montiel, Antonio (Frontiers in Molecular Neuroscience, 2022)
Chronic pain and pruritus are highly disabling pathologies that still lack appropriate therapeutic intervention. At cellular level the transduction and transmission of pain and pruritogenic signals are closely intertwined, negatively modulating each other. The molecular and cellular pathways involved are multifactorial and complex, including peripheral and central components. Peripherally, pain and itch are produced by subpopulations of specialized nociceptors that recognize and transduce algesic and pruritogenic signals. Although still under intense investigation, cumulative evidence is pointing to the thermosensory channel TRPV1 as a hub for a large number of pro-algesic and itchy agents. TRPV1 appears metabolically coupled to most neural receptors that recognize algesic and pruritic molecules. Thus, targeting TRPV1 function appears as a valuable and reasonable therapeutic strategy. In support of this tenet, capsaicin, a desensitizing TRPV1 agonist, has been shown to exhibit clinically relevant analgesic, anti-inflammatory and anti-pruritic activities. However, potent TRPV1 antagonists have been questioned due to an hyperthermic secondary effect that prevented their clinical development. Thus, softer strategies directed to modulate peripheral TRPV1 function appear warranted to alleviate chronic pain and itch. In this regard, soft, deactivatable TRPV1 antagonists for topical or local application appear as an innovative approach for improving the distressing painful and itchy symptoms of patients suffering chronic pain or pruritus. Here, we review the data on these compounds and propose that this strategy could be used to target other peripheral therapeutic targets.